Constitutional Contestation of the Islamic State Concept in the Indonesian Parliament 1956-1959 - Anshori, Ahmad Yani; Abdurrahman, Landy Trisna (Shariah Faculty UIN Maulana Malik Ibrahim Malang, 2024)
Among the most historic events that today's young generation of Muslims may largely forget is the unanimous agreement of various Islamic factions in the struggle to establish Islam as the basis of the state and Islamic law (Sharia) as the country's constitution in the forum of the Indonesian Constituent Assembly. This study examines the substance and urgency of that contestation, particularly regarding the concept of an Islamic State and the proposed framework of Islamic law. Utilising a qualitative methodology that combines historical and normative approaches. The data sources for this research consist of documents from the Constituent Assembly, political speech archives, and other relevant records, which are validated through source triangulation to ensure their reliability. The findings indicate that all Islamic factions were united in their desire to establish a state based on Islamic principles, specifically an egalitarian state with pluralism as its foundation, a state that guarantees the enforcement of Islamic law, a state that adheres to theistic democracy, and a state that adopts an Islamic economic system. This contestation influenced the outcomes of constitutional discussions and acted as a catalyst in shaping the character of political Islam in Indonesia, both in its accommodating forms and its oppositional stance towards the state. This research offers an important historical perspective for the study of contemporary Indonesian governance, particularly in integrating inclusive democratic Islamic values into the framework of the state and in alleviating the theological tensions experienced by some Indonesian Muslims as both religious community (Islamic umma) and state citizens—tensions that have often been a major trigger for conflicts between Islam and the state in Indonesia, both past and present.